Penyebab dan dampak bullying pada remaja di lingkungan sekolah dengan metode scoping review - Saputri, Zahwa Isnazwa (Maliki Interdisciplinary Journal, 2024)
in adolescents in the school environment. This study uses the Scoping Review method to explore the causes and impacts of bullying behavior on teenagers in the school environment. Through searches in various basic data, articles and related literature, it was found that there are several factors that cause bullying in schools, including individual factors such as physical differences, intelligence or sexual orientation, as well as environmental factors such as lack of supervision from teachers and school staff. , as well as an unsupportive school culture. Research also highlights the far-reaching impact of bullying on teenagers, both physically and psychologically, such as mental disorders, decreased self-confidence, decreased academic performance, and even in extreme cases, can cause feelings of hopelessness that can lead to suicide. These findings indicate the need for a holistic approach in overcoming the problem of bullying, including interventions that involve the active role of schools, families and society as a whole to create a safe and supportive environment for adolescents in the school environment.